Investigation of rotation at the plasma edge in TCABR. (30th July 2015) - Severo, J.H.F.; Ronchi, G.; Galvao, R.M.O.; Nascimento, I.C.; Guimaraes-Filho, Z.O.; Kuznetsov, Yu.K.; Nave, M.F.F.; Oliveira, A.M.; Nascimento, F. do; Tendler, M.
Abstract: This paper summarizes experimental results from recent studies on intrinsic rotation at the plasma edge of the TCABR tokamak. These results were obtained after upgrading the number of channels of the rotation diagnostic to three. The measurements were carried out in the collisional (Pfirsch–Schluter) regime and the rotation profiles of the ions were obtained from the Doppler shifts of the impurity carbon lines, CIII (464.74 nm), and CVI (529.06 nm). Results on the correlation between toroidal rotation at the plasma edge and direction of gas injection are also presented. They indicate that the direction of gas injection has a small effect on rotation; the velocity of the background neutral hydrogen is affected by direct momentum transfer from the injected gas (also hydrogen), while the carbon ions' velocity is affected by inward radial friction force between the injected gas atoms and ions, increasing their velocity in the opposite sense of the plasma current.